Viewing photos and reading nouns of natural graspable objects similarly modulate motor responses - Marino, Barbara F. M.; Sirianni, Miriam; Volta, Riccardo Dalla; Magliocco, Fabio; Silipo, Francesco; Quattrone, Aldo; Buccino, Giovanni (Frontiers in Human Neuroscience, 2014)
It is well known that the observation of graspable objects recruits the same motor representations involved in their actual manipulation. Recent evidence suggests that the presentation of nouns referring to graspable objects may exert similar effects. So far, however, it is not clear to what extent the modulation of the motor system during object observation overlaps with that related to noun processing. To address this issue, 2 behavioral experiments were carried out using a go-no go paradigm. Healthy participants were presented with photos and nouns of graspable and non-graspable natural objects. Also scrambled images and pseudowords obtained from the original stimuli were used. At a go-signal onset (150 ms after stimulus presentation) participants had to press a key when the stimulus referred to a real object, using their right (Experiment 1) or left (Experiment 2) hand, and refrain from responding when a scrambled image or a pseudoword was presented. Slower responses were found for both photos and nouns of graspable objects as compared to non-graspable objects, independent of the responding hand. These findings suggest that processing seen graspable objects and written nouns referring to graspable objects similarly modulates the motor system.